1996
DOI: 10.1002/marc.1996.030170507
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization and copolymerization of ethene initiated with disiloxane‐bridged biscyclopentadienylzirconium complexes and methylaluminoxane

Abstract: The disiloxane-bridged zirconocene complexes, tetramethyldisiloxanediylbis(cyclopentadieny1)zirconium dichloride and tetramethyldisiloxanediylbis(cyc1opentadienyl)dimethylzirconium initiate the homopolymerization of ethene as well as the copolymerization of ethene and a-olefin with a modified methylaluminoxane as cocatalyst. The catalyst systems give resonable activity but the molecular weight of polyethene decreases drastically with increasing polymerization temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 8 publications
0
2
0
2
Order By: Relevance
“…A longer alkylidene or polysiloxane bridge improves the catalytic activity of dinuclear metallocenes which was discovered by Noh eta l 21‐25. and Alt et al11, 12 However, we found that the composition of the bridge is more important than their length.…”
Section: Resultsmentioning
confidence: 41%
“…A longer alkylidene or polysiloxane bridge improves the catalytic activity of dinuclear metallocenes which was discovered by Noh eta l 21‐25. and Alt et al11, 12 However, we found that the composition of the bridge is more important than their length.…”
Section: Resultsmentioning
confidence: 41%
“…Zweikernige Metallocenkomplexe mit 2,2-Cyclopentadienyl-Indenyl-Propan und Cyclopentadienyl-indenyldimethylsilan als Ligandvorstufen wurden von Green auf ihr Ethylen-und Propylenpolymerisationspotential getestet [26,27]. Systematische Untersuchungen zu den Polymerisationseigenschaften dinuklearer polysiloxanverbr€ uckter Katalysatoren wurden von Noh durchgef€ uhrt [28][29][30][31][32][33][34].…”
Section: Einf€ Uhrungunclassified
“…Dagegen ermö glichen es verbrü ckte Biscyclopentadienylliganden durch Veränderung der Brü ckenlänge oder der Art der Brü cke die räumliche Trennung der beiden Metallzentren in einem weiten Bereich zu beeinflussen [1]. Noh zweikerniger polysiloxanverbrü ckter Metallocenkatalysatoren von der Länge der Brü cke abhängig sind [14][15][16][17][18][19][20]. Die Brü ckenlänge ist also ebenso wie die Art des Zentralmetalls [21][22][23] oder die Art und Position der Substituenten am Liganden [24,25] ein entscheidender Parameter in der metallocenkatalysierten Polymerisation von Olefinen [26].…”
Section: Einführungunclassified